Pengaruh Kedisiplinan Kerja dan Motivasi Terhadap Kinerja Pegawai (Studi Kasus Pada SMP Negeri 3 Surakarta) - Ramatha, Erga Adnan, Drs. Ma‟aruf, MM (2016)
This research aims to find out: 1) the influence of the discipline of work on performance clerk; 2) influence the motivation of working against the performance of employees; and 3) the influence of the discipline of work and motivation on performance clerk in SMP Negeri 3. Type of this research is a survey research with quantitative approach. The population in this study are all the employees in the SMP Negeri 3 Surakarta which consists of 112 people. The sample in this research totaled 53 people who were selected using random sampling techniques. The technique of data collection conducted using questionnaires. Technique of data analysis performed multiple linear regression using two predictors, test F, t-test, and the coefficient of determination (R2). Based on the results of the analysis, this study concludes that: 1) there is a significant and positive influence on performance of work discipline employees; 2) there is significant motivation and a positive influence on performance clerk; 2) there is a significant and positive influence of the discipline of work and motivation together on performance clerk in SMP Negeri 3. Key words: work, discipline, performance motivation.